Burning characteristics of biogas with addition of hydrogen - Goh, Shong Wei, author 611840; Chong, Cheng Tung, supervisor 414459; Fakulti Kejuruteraan Mekanikal 8081 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper